Analysis and characteristics of tars collected during a pilot-scale underground coal gasification (UCG) trial. (15th November 2017) - Wiatowski, Marian; Kapusta, Krzysztof; Stańczyk, Krzysztof
Highlights: A pilot-scale UCG experiment in an operating coal mine was conducted. The influence of gasification time on tar properties was studied. The amount of tar remaining underground was evaluated. A temperature of gasification was estimated. Abstract: This paper presents the results of six tar sample analyses obtained during 60 days of an underground coal gasification (UCG) trial in the "Wieczorek" mine in Poland. The tars were sampled periodically during coal gasification by four different reagents: oxygen enriched air, air, a mixture of air and carbon dioxide, and air with nitrogen. The tar samples were analysed over a wide range of physico-chemical parameters typical for the assessment of the quality of coke-oven tar. It was observed that due to tar fractionation, only approximately 40% of the produced tar condensed on the surface. The tar obtained during coal gasification by air mixed with carbon dioxide demonstrated analysis results different than the other tars. The resulting tars were characterized by a high average calorific value of 39 MJ/kg, which is higher than that for the typical coke-oven tar (approximately 36.0 MJ/kg). A positive test of miscibility of tar from UCG with coke-oven tar enables consideration of their co-processing. It was estimated that the temperature in the pyrolysis zone could be in the range of 700–1000 °C. This study also revealed that tars were subjected to secondary reactions in which cracking processes dominated over the gasification time.